Formaldehyde Emission and Properties of Phenol Formaldehyde-Treated Oil Palm Wood - Amarullah, Mohamad (2010)
It is known that impregnation of oil palm wood (OPW) with low molecular weight phenol formaldehyde (Lmw-PF) resin significantly improved the strength, dimensional stability, durability, and machining characteristics of the material. This treatment has shown a great potential to expand the usage of OPW for high-grade furniture and housing materials. However, the treated OPW releases high amount of formaldehyde emission (FE), i.e. more than 30 mg/L which is considered as mammalian hazardous. If this material is to be used for indoor application, its FE should be reduced to threshold limit of 0.1 mg/L or less. The main objective of this study was to determine the level and reduce the FE from phenol formaldehyde-treated OPW which was manufactured at different processing variables. The physical properties such as density percent gain, weight percent gain, water absorption, thickness swelling, density profile, and mechanical properties such as modulus of elasticity (MOE), modulus of rupture (MOR), compression strength, shear strength, and hardness of the treated OPW were also assessed. In this study two approaches were carried out to reduce the FE. Firstly, by improving the cur ng state of the resin through a modification of compression step and adopting a post treatment drying after the manufacturing. Secondly, incorporating urea in the treating solution (as formaldehyde catcher). Samples were treated with 15% w/w Lmw-PF using vacuum pressure. After treatment,the samples were dried with industrial microwave until reach moisture content of 50%. The samples were then hot pressed at 150°C for 45 min to a compression ratio 50% (from 40 to 20 mm thick) using various compression steps (12.5%-25%-50%, 12.5%-37.5%-50%, and 25%-50%). The compression steps were varied in combination with various post treatment drying (0, 24, and 48 h) in an oven at 103 ± 2°C. The compression step of 12.5%-25%-50% produced the sample with the lowest FE, and it was choosen as the optimum compression step which would be used in the second study. For the second approach, the treatment with the optimum compression step (12.5%-25%-50%) was combined with addition of various concentration of urea granule (5, 10, and 15% based on solid weight of phenol) in the treating solution as formaldehyde catcher. The results showed that implementation of post treatment drying and modifying compression step significantly (P < 0.05) reduced FE level of the treated OPW from 30 to 9 mg/L. It is acknowledged that the post treatment drying gave more effect on reduction of FE than that of modifying compression step. The sample treated using combination of compression step of 12.5%-25%-50% and post treatment drying of 48 h emited the lowest FE of 9 mg/L. Meanwhile the addition of urea was not significantly (P > 0.05) reduces the FE level of the samples. In term of physical properties, it was found that the three type treatments (altering compression step, post drying treatment, and addition of urea granule) imparted various positive and negative effects on the properties of the treated OPW. In general, there was no significant effect (P > 0.05) of the compression step and post drying treatments on the density gain, but the additions of urea granule on the PF resin liquid increased the sample density gain. The compression step gave more effect on the resin load than the post treatment drying, and the addition of urea granule on the PF liquid only increased the resin load. The microwave pre-heating prior to the hot-pressing nsification resulted in the better (shallower) density profile of the treated OPW than that of many particleboards. The thickness swelling (TS) and water absorption (WA) values of the treated OPW were not affected by the three treatments. In term of mechanical properties, the three treatments also imparted various positive and negative effects on the properties of the treated OPW. Both the compression step and post treatment drying gave significant effects (P < 0.05)on bending strength (MOE and MOR) values of the treated OPW samples, in which the former gave more significant effects than the later. Combination of the compression step of 12.5%---+25%---+50% and post treatment drying of 48 h gave the highest MOE value (14,980 MPa), and compression step of 12.5%---+25%---+50% and post treatment drying of 0 h gave the highest MOR value (121.08 MPa). The post treatment drying gave irregular effect of the MOE but it has negative effect on MOR due to cellulose degradation caused by long heating treatment. Whilst, addition of urea granule on the resin liquid gave no significant (P > 0.05) effect on both the MOE and MOR values of treated OPW. The compression strengths were mainly affected by post treatment drying, and there was a tendency that the longer post treatment drying gave the higher compressive strength. The post treatment drying gave a positive effect, but urea granule addition gave negative effect on the shear strength of the treated OPW. All the three treatments gave no significant effect (P > 0.05) on the hardness of the treated OPW. Compare to the untreated OPW, the impregnation treatment of the OPW with Lmw-PF resin increased the MOE for 5.5 times (from 2,157 MPa to 11,954 MPa), MOR for 6.1 times (from 15.9 MPa to 97.4 MPa), compression strength parallel to the grain for 5.6 times (from 15.7 MPa to 88.1 MPa), and shear strength for 5 times (from 2.0• MPa to 10 MPa). Finally, It can be concluded that implementation of post treatment drying and modifying compression step significantly reduced the FE level and increased the physical and mechanical properties of OPW. The modified impregnation treatment can be applied to effectively modify low quality OPW into highgrade OPW that can be used as value added furniture and other high grade interior/exterior applications.